Analisis Ketahanan Equipment Ballmill terhadap Pengaruh Oprasional Boiler dalam Penerapan Reability Centered Metode (RCM) Menggunakan Soft System Methodology - Muhammad Shodikin; Muhamad Alfarizi; Andi Laupe; Lucky Setiawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
PT. Dian Swastatika Sentosa generates electricity through a private thermal power plant. This company produces steam and electricity for paper mills. The company hopes to meet its steam and electricity needs in 2023 with a boiler with a load capacity of 180 tons and a maximum capacity of 220 tons. However, from February to July 2023, that goal was not achieved. The most common problems faced by this company are the failure to conduct preventive inspections and timely machine maintenance, as well as the failure to carry out necessary repairs. Delays in machine repairs, which result in inconsistent machine downtime schedules to meet customer demand, leading to damage to boiler equipment, causing abnormal boiler operation and reduced steam production. This research aims to design equipment to withstand operational impacts using failure mode and effects analysis (FMEA) with the Soft Systems Methodology (SSM) and reliability-centered maintenance (RCM) techniques. The RCM method assists in identifying the processes that must be followed to guarantee that a machine or system performs as intended. RCM can also be used to design, choose, and create alternative maintenance methods that are focused on safety, operations, standards, and economics. For the entire problem in the investigation, a dynamic model is necessary. An analytical system is used in this model in order to recognize and duplicate the features of the overall system., as well as to provide repair solutions and address the burden of the problem. This research produces a presentation in the form of problem identification, causal loops, diagrams of machines that frequently experience failures, rich images of the causes and effects of the ball plate crusher liner damage, root cause definitions, and conceptual models for repair and maintenance. business productivity and debating process.